Nephroprotective Effects and Its Mechanism of an Herbal Prescription on Diabetic Nephropathy Rats - Cai, H.Z.; Wang, S.K.; Sheng, J.L.; Huang, P.L.; Sun, G.J. (Asian Journal of Chemistry, 2012)
The work aims at investigating protective effects and mechanism of an herbal prescription (162.5 mg/kg-650 mg/kg bw/d) composed of tea and lycium bararum polysaccharides and Eucommia ulmoides on diabetic nephropathy. Following parameters were measured: (1) body weights, 24 h's urine volume, urine protein, serum glucose and insulin levels, blood urea nitrogen, serum creatinine, advanced glycosylation end products (AGEs); (2) kidney weight, aldose reductase and protein kinase C in kidney tissue; (3) histopathology of kidney. Body weight and albuminuria of diabetic nephropathy rats were improved and blood glucose, blood urea nitrogen and serum creatinine were decreased. Excretion and sensitivity to insulin was activated. Moreover, the prescription evoked normalisation of diabetes-stimulated kidney NADPH oxidase and reduced levers of advanced glycosylation end products and percentages of cell membrane protein kinase C activity accounted for gross activity. It also restrained thickening of glomerular mesangial area and basement membrane and degeneration of tubular. The prescription seems to be benefit for preventing development of diabetic nephropathy.